Vanadium Oxide Nanofibers: Synthesis and Research on Functional Properties - Berezina, O. Ya.; Markova, N.P.; Kolobova, E.N.; Pergament, A.L.; Yakovleva, D.S.; Zlomanov, V.P.; Krivoshchapov, N.V. (Micro and Nanosystems, 2020)
Aim: Vanadium oxide nanofibers have been manufactured by the sol–gel electrospinning method followed by the thermal treatment in air and argon. Materials and Methods: The samples are characterized by optical, laser confocal and scanning electron microscopy, energy-dispersive X-ray elemental analysis, X-ray diffraction, cyclic voltammetry, and electrical conductivity measurements. Results: The obtained VO2 nanofibers demonstrate the semiconductor-to-metal phase transition. Also, the vanadium pentoxide nanofibers are examined as electrode materials for rechargeable Li-ion batteries.
Keywords: Li-ion batteries